Application of the Modified Andreasen Packing Model for Optimizing Strength and Cost of Normal Concrete with Uniformly Graded Aggregates - Acjaisah; I Ketut Hendra Wiryasuta; Mirza Ghulam Rifqi (Universitas Sulawesi Barat, 2026)
Concrete containing uniformly graded coarse aggregates generally exhibits low packing density and high porosity, which adversely affect compressive strength. Despite these limitations, such aggregate conditions are often unavoidable in practice due to material availability constraints, necessitating optimized mix design approaches to enhance mechanical performance and cost efficiency. This study aims to optimize the mix design of normal concrete with uniformly graded coarse aggregates based on SNI 03-2834-2000 using the Modified Andreasen Packing Model (MAPM), with emphasis on compressive strength and material cost evaluation. A total of 18 cylindrical specimens were tested at curing ages of 3, 14, and 28 days, with a target compressive strength of 20 MPa. At 3 days, compressive strengths of 8.10 MPa and 8.93 MPa were obtained for the SNI and MAPM methods, respectively. At 14 days, the SNI method achieved 15.48 MPa, while MAPM reached 26.90 MPa. At 28 days, the SNI method produced 19.37 MPa, whereas MAPM achieved 30.96 MPa, exceeding the target strength. In terms of material cost, the SNI method required IDR 704,212, while MAPM required IDR 675,256, resulting in a cost reduction of IDR 28,956. These findings demonstrate that MAPM significantly enhances compressive strength while reducing material costs under non-ideal aggregate conditions.